Pengaruh Budaya Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada PT.PLN Indonesia Power UBP Keramasan - Rosa, Alkirma; Roni, Mukran (CV. ITTC INDONESIA, 2024)
The purpose of this research is to determine the influence of work culture and work environment on employee performance, the object of research at PT. PLN Indonesia Power Generation Business Unit (UBP) Keramasan Palembang, the research sample is employees of PT. PLN Indonesia Power UBP Keramasan, with a total of 83 employees, the method used is a quantitative method using the SPSS Version 27 technique. The data used is primary data, hypothesis testing uses the t test (partial) and the f test (simultaneous). The analysis results show that work culture and work environment have a positive and significant effect on employee work.